Oral health knowledge, literacy and behavior of pregnant women: a qualitative study in a northeastern province of Thailand - Nitikorn Phoosuwan; Pimchanok Bunnatee; Pranee C. Lundberg (BMC, 2024)
Abstract Background Pregnancy is a unique period of women's lives, and oral health is an important public health indicator during this period. Pregnant women have increased vulnerability to oral health problems. The study aimed to describe oral health knowledge, literacy and behavior of pregnant women in a northeastern province of Thailand. Methods A descriptive study was used. Twenty pregnant women who attended antenatal care clinics of eight public hospitals in the province were recruited by use of purposive sampling. They participated voluntarily in individual interview. The Health Belief Model was used as conception framework. All data were transcribed and subjected to content analysis. Results Five categories emerged: Misbelief and lack of knowledge, Oral health problems and dental care seeking, Oral health information from different persons, Self-care management of oral health, and Fear of and anxiety towards dental treatment. The findings showed that low knowledge of need for treatment, little importance to oral health and low priority of dental needs affect the demand for dental care. Fear of and anxiety towards dental treatment were the results of negative past experiences of neglecting dental care. Some women perceived health benefits of practicing self-care of oral health during pregnancy. Conclusion The findings help to better understand the oral health issues of pregnant women and provide baseline information for oral health promotion. Such promotion and culturally appropriate care should be integrated in maternal health education classes.